2019
DOI: 10.1097/cm9.0000000000000332
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of osteoporotic vertebral fracture among community-dwelling elderly in Shanghai

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 11 publications
3
26
1
Order By: Relevance
“…There is evidence that, despite greater soft tissue mass and thickness, obesity is not protective against fracture, particularly at the spine and appendicular skeletal sites [17][18][19]. A recent study in Shanghai, China, reported that the prevalence of vertebral deformity in men was similar to that in women (17% vs. 17.3%) over 60 years [26] and a three-fold higher vertebral fracture prevalence in men has been reported elsewhere [17].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that, despite greater soft tissue mass and thickness, obesity is not protective against fracture, particularly at the spine and appendicular skeletal sites [17][18][19]. A recent study in Shanghai, China, reported that the prevalence of vertebral deformity in men was similar to that in women (17% vs. 17.3%) over 60 years [26] and a three-fold higher vertebral fracture prevalence in men has been reported elsewhere [17].…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria were as follows: healthy men and women according to the following excluding criteria. Exclusion criteria in accordance with our previous articles were used to exclude individuals from the study [ 5 , 16 , 19 , 20 ]: (1) serious effects from cerebrovascular disease; (2) other diseases, such as diabetes mellitus, chronic renal disease, chronic liver disease, rheumatoid arthritis or collagen disease, hyperthyroidism, and recent major gastrointestinal disease; (3) evidence of other metabolic or inherited bone diseases; (4) significant diseases of any endocrine organ that would affect bone mass; (5) any neurological or musculoskeletal condition; and (6) any form of calcium and vitamin-D therapy in three months or taking antiosteoporotic drugs (e.g., bisphosphonates, selective estrogen receptor modulators, and calcitonin). Postmenopausal women who had experienced early menopause (before 45 years of age) were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Our study showed that the prevalence of vertebral fracture was 17.2% among Shanghai community-dwelling elders (over 60 years), 17.0% for males, and 17.3% for females. The prevalence among females increased with age [ 5 ]. The prevalence of osteoporosis in our country has increased over the past 12 years, affecting more than one-third of people aged 50 years and older [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the prevalence is higher in rural areas of China, at 20.7% and 35.3%, respectively, which may indicate a relatively poor bone health situation of countryside inhabitants. Our former study concentrated on vertebral fractures in approximately 15,000 Shanghai community-dwelling elderly individuals and found a prevalence of 17.0% for males and 17.3% for females, and rural areas also obtained a higher prevalence than downtown areas in Shanghai ( 4 ). Bone mineral density (BMD) measured by dual energy X-ray absorptiometry (DXA) remains the gold diagnostic standard for osteoporosis according to a report about the assessment of fracture risk and its application to screening for postmenopausal osteoporosis from the World Health Organization in 1994.…”
Section: Introductionmentioning
confidence: 95%